LEADING TO TRANSFORM: LEADERSHIP PRACTICES AND MEXICAN HUMANISM IN TECHNOLOGICAL EDUCATION - Montufar, Gilberto Rodríguez (Seven Editora, 2026)
The chapter analyzes how leadership practices can guide the transformation of technological education toward Mexican Humanism, considering the National Technological Institute of Mexico (TecNM) as an institutional case study. The objective is to interpret how normative guidelines and the transversal axes of the educational model are translated into operational management criteria, shaping the identity of the leadership body and its capacity to act within complex organizational contexts. The theoretical-analytical approach is interpretive and is grounded in documentary analysis of the TecNM Educational Model, in dialogue with recent literature on educational leadership, public ethics, social justice, and implementation governance. The analytical axes are organized around: (i) leadership practices and the construction of a humanistic leadership identity; (ii) critical thinking as continuous training to understand the determinants of educational service delivery and to support legitimate decision-making; (iii) institutionalized dialogue and collaborative work as organizational technologies for coordination among members of the leadership body, faculty, and administrative staff; and (iv) social responsibility, equity, environmental awareness, and socially relevant innovation as stable management criteria. As a contribution, the chapter proposes an integrative conceptual model of humanistic leadership practices that brings together public values, leadership identity, and organizational mediations. It is argued that this articulation strengthens institutional legitimacy, institutional and collective well-being, and guides coherent, inclusive, and socially relevant processes of educational transformation in Mexican public technological institutions. Although grounded in the TecNM case, the proposed conceptual model seeks to offer an analytical lens transferable to public technological education institutions in other national contexts facing comparable organizational challenges. DOI: https://doi.org/10.56238/sevened2026.008-109